The Effect of Nurses' Motivation and Performance on the Application of Professional Nursing Practice Models at the Tangerang City Regional General Hospital - Pipit Pitriani; Fitri Arofiati; Giri Widagdo (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2025)
Background: Nursing services are the spearhead of health services in hospitals, quality and professional services are needed by developing a Professional Nursing Practice Model. The successful application of the Professional Nursing Practice Model is supported by high motivation from nurses, so that it will produce a good performance in accordance with the objectives to be achieved. The purpose of this study was to determine the effect of nurses' motivation and performance on the application of professional nursing practice models at the Tangerang City Regional General Hospital Objectives: Methods: This study was cross sectional, with 90 respondents. The analysis used multiple logistic regression. Results: From the results of the multivariate analysis in this study, it is known that the level of education and length of work are confounding. Based on the multiple logistic regression test, it is known that the OR value of 4.263 means that a strong nurse's motivation can have the opportunity to apply the Professional Nursing Practice Method of 4.2 times compared to a weak nurse's motivation after being controlled by the level of education and length of work and it is also known that the OR value of 4.054 means that the nurse's performance is low. Good nurses have the opportunity to apply Professional Nursing Practice Methods by 4 times compared to weak nurses' performance after being controlled by education level and length of work Conclusion: The most dominant variable that influences the application of the professional nursing practice model is the motivation of nurses with an OR of 4.263.